Socialization of Early Marriage as an Effort to Reduce the Rate of Early Marriage at SMPN 2 Satap Kayangan - Syahrani, Dania; Hatimah, Husnul; Mulyono, Ana; Khaeratul, Riza; Wulandari, Shely; Insani, Tazkiatun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Early marriage is a social problem that occurs very often both in urban and rural areas, including in Pendua Village. The aim of this community service is to convey about the disadvantages and negative impacts of early marriage. Through outreach using early marriage educational film screening techniques, it is hoped that it will provide awareness for middle-level students to local communities regarding the impact of early marriage. The method applied is socialization by showing educational films related to early marriage. The targets of this socialization are middle-level students in Pendua Village. The results of socialization show that early marriage has more negative impacts on both the bride and groom and their future offspring. From these outreach efforts, it is hoped that there will be increased awareness among students and the public regarding the negative impacts of early marriage and strengthen support for preventive measures.